Chronicle of the 20th Century - Editor in Chief Mercer, Derrik (France JOL International Publications, 1988)
A presentation of the world's events in the 20th-century, this book records such events as technical leaps and geopolitical reversals. It also focuses on important and famous people of the century.
Includes Colored Illustrations and Index.
Keywords: History, Modern